Four new species of the Euconnus taiwanus group from China (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2024)
Six Eastern Palaearctic species of the Euconnus taiwanus group are known to occur in Taiwan, China and Japan. Four more species are described based on specimens collected in China: E. (s. str.) baoshanus sp. nov. (Yunnan), E. (s. str.) pseudobaoshanus sp. nov. (Yunnan), E. (s. str.) tianmushanus sp. nov. (Zhejiang), and E. (s. str.) pingbianensis sp. nov. (Yunnan).